Experiences and Perspectives on Spodoptera frugiperda (Lepidoptera: Noctuidae) Management in Sub-Saharan Africa - Njuguna, Elizabeth; Nethononda, Phophi; Maredia, Karim; Mbabazi, Ruth; Kachapulula, Paul; Rowe, Arielle; Ndolo, Dennis (Journal of Integrated Pest Management, 2021)
It has been over five years since the first report of an outbreak of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) in Africa. The highly invasive pest, native to the Americas, has since spread across the African continent attacking many crops and causing significant yield loss to Africa’s staple crop, maize. From the onset of the outbreak, there have been massive and varied responses from farmers, governments and nongovernmental organizations. This mini-review provides various perspectives on S. frugiperda control in sub- Saharan Africa, building on previously published evidence, and experiences of the authors. It also highlights new technologies and lessons learned so far from the S. frugiperda outbreaks in sub-Saharan Africa, based on which suggestions on possible integrated management approaches are proffered.
Keywords: Biopesticide; Fall armyworm; Integrated pest management; Invasive; Sub-Saharan Africa